An Ultra‐Thin Stretchable Electrode Based on High‐Resilient Polyurethane Crosslinked with La 3+ ‐Complexes - Huang, Qi‐Sheng; Yang, Ruohan; Yang, Zhi‐Dong; Zhao, Pei‐Chen; Wang, Xiaoliang; Li, Cheng‐Hui (Small (Weinheim an der Bergstrasse, Germany), 2025)
Stretchable electronic skins with multifunctional sensing capabilities are of great importance in smart healthcare, wearable display electronics, intelligent robots, and human‐machine interfaces. Thermoplastic elastomers play a pivotal role as soft substrate in the field of stretchable electronics. However, the dynamic interactions of common thermoplastic elastomers often result in high hysteresis and fatigue damage, limiting their performance and durability. In this study, a highly resilient and fatigue‐resistant elastomer is developed by employing La 3+ ‐complexes as crosslinkers. The woven structure formed between the prepolymer ligands and lanthanum (III) metal ions establishes stable coordination interactions and introduces additional entanglements around the coordination crosslinkers. Furthermore, this woven structure self‐assembles into hierarchical nanoarchitectures, which serve as physical crosslinks, significantly enhancing the mechanical strength. As a result, the new elastomers exhibit exceptional mechanical strength (Young's modulus ≈3.47 MPa; maximum stress ≈16.52 MPa), resilience (residual strain during cyclic stretching at 100% strain ≈8%), fatigue resistance (strength retention rate ≈90% after 2000 cycles stretching), and stable thermomechanical properties (creep strain ≈14.43% and residual strain ≈0.22% at 80 °C 0.1 MPa). Leveraging this high‐performance polyurethane elastomer, ultra‐thin flexible electrodes are fabricated, which can achieve stable and long‐term monitoring of the physiological signals of human body.